The role of peripheral blood eosinophil counts in acute Stanford type A aortic dissection patients - Qin, Xichun; Gao, Yaxuan; Jiang, Yi; Zhu, Feng; Xie, Wei; Tang, Xinlong; Xue, Yunxing; Wang, Dongjin; Cao, Hailong (Frontiers in Surgery, 2022)
Background: Acute Stanford-A aortic dissection (AAAD) is a devastating cardiovascular condition with high mortality, therefore identifying risk prognosis factors is vital for the risk stratification of patients with AAAD. Here, we investigated peripheral blood eosinophil (EOS) counts in patients with AAAD and their possible biological implications. Methods: We performed a single center retrospective cohort study. From 2011 to 2021, a total of 1190 patients underwent AAAD surgery. Patients were categorized first by death and then admission EOS counts (0.00 × 109/L or > 0.00 × 109/L). Demographics, laboratory data, and outcomes were analyzed using standard statistical analyses. Ascending aorta specimens were used for western blotting and histological assessments. Results: Death group patients had lower EOS counts than the non-death group (P = 0.008). When patients were stratified using mean blood EOS counts: 681 patients had low (0.00 × 109/L) and 499 had high (> 0.00 × 109/L) counts. Patients with low EOS counts at admission were more likely to have a higher mortality risk (P = 0.017) and longer treatment in the intensive care unit (ICU) days (P = 0.033) than patients with normal EOS counts. Also, the five blood coagulation items between both groups showed significantly different (P < 0.001). Hematoxylin & eosin-stained cross-sections of the ascending aorta false lumen showed that EOSs were readily observed in thrombi in the false lumen of the aorta. Conclusions: Peripheral blood EOS counts may be involved in thrombosis and could be an effective and efficient indicator for the diagnosis, evaluation, and prognosis monitoring of patients with AAAD.